The risk of pneumococcal infections after immunization with pneumococcal conjugate vaccine compared to non-vaccinated inflammatory arthritis patients. (July 2015) - Nagel, J; Geborek, P; Saxne, T; Jönsson, G; Englund, M; Petersson, IF; Nilsson, J-Å; Kapetanovic, MC
<x xml:space="preserve">Abstract</x> Objectives: To examine the risk of putative pneumococcal infections in adult arthritis patients on different anti-rheumatic drugs immunized with heptavalent pneumococcal conjugate vaccine (Prevenar 7; PCV7) and non-vaccinated individually matched arthritis patients. Method: All individuals in a cohort of 505 patients with rheumatoid arthritis (RA) or spondylarthropathy (SpA) receiving different anti-rheumatic treatments were immunized with a single dose of PCV7 (exposed group). Of these, 497 patients (RA = 248; SpA = 249) were included. For each vaccinated patient, we identified four reference subjects (n = 1988) from the same geographic area, individually matched for age, gender, and diagnosis. These were considered unexposed to conjugated pneumococcal vaccination. The Skåne Healthcare Register (SHR) was searched for all individuals seeking health care for putative pneumococcal infections occurring 4 years before vaccination and up to 4.5 years after vaccination using ICD-10 diagnostic codes. The following infections were considered as serious cases: pneumonia, other lower respiratory infections, meningitis, sepsis, and septic arthritis. The relative risk (RR) of infection was calculated as the number of events after/number of events before vaccination. Ratios of relative risk (RRRs) were calculated between vaccinated and non-vaccinated groups of patients. A generalized estimating equation (GEE) was used to handle correlated data for several events in the same individual. Results: Although statistically non-significant, the point estimate of the RRR [0.55, 95% confidence interval (CI) 0.25–1.22] suggested a reduced risk of serious pneumococcal infections in vaccinated patients compared to the unexposed group. Conclusions: Vaccination with PCV7 tended to reduce the risk of putative serious pneumococcal infections by about 45% compared to non-vaccinated patients in this observational cohort study.